Design and Error Compensation Performance of a Precision Micro-Drive Rotary System. (20th July 2021) - Yang, Manzhi; Jing, Gang; Lv, Zhenyang; Guo, Wei; Huang, Yumei; Wei, Kaiyang; Li, Linyue; Feng, Bin; Ge, Hongyu; Li, Shuaitian
Abstract : In order to obtain motion with large travel and high precision, the micro-drive system is used to compensate for the motion error of the macro-drive system in the macro/micro dual-drive system. The research on the micro-drive rotary system lags behind the micro-drive linear system, so it is of great significance to study the designing and error compensation performance of a precision micro-drive rotary system. In this paper, a precision micro-drive rotary system is designed, the error compensation scheme of the system is proposed, and the system feasibility in design and error compensation is tested by FEM simulation analysis and performance experiments. Firstly, a precision micro-drive rotary system is designed to provide high-precision rotary motion, which consists of a micro rotary mechanism and PZT. In the system, the micro rotary mechanism is developed based on the compound motion principle of flexure hinge, which can accurately transform an input of linear motion into an output of rotary motion according to a certain relationship. Secondly, for finishing the error compensation scheme of the system, the maximum compensation modifier θ max ′ is proposed based on the analysis of error compensation equations of point-to-point motion and continuous motion. Finally, in order to facilitate the use of engineering, the driven voltage equation of error compensation is derived by the error compensation performance experiment. The simulation and experiment results indicate that both the design and error-compensation-range of the system satisfy the needs of practical application.